2023
DOI: 10.3390/ijms24108665
|View full text |Cite
|
Sign up to set email alerts
|

The Preventive Role of the Vitamin D Endocrine System in Cervical Cancer

Euclides Avila,
Bryan Javier Noriega-Mejía,
Jocelyn González-Macías
et al.

Abstract: Vitamin D along with its active metabolite calcitriol and its metabolic and signaling system, known as the vitamin D endocrine system, have been widely recognized as a pivotal regulator of calcium homeostasis in addition to non-calcemic antitumoral effects in a variety of human cancers, including cervical cancer. Several studies have found an inverse relationship between the incidence of cervical neoplasia and vitamin D levels. This narrative review updates the current evidence supporting the notion that the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…In addition, the beneficial effect of EGCG on cells was further enhanced when vitamin D was taken at the same time [ 128 ]. Optimal levels of vitamin D have been shown to help prevent and regress low-grade squamous intraepithelial lesions of the cervix and reduce the risk of fibroids [ 266 ]. However, there is no clear statement of the exact mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the beneficial effect of EGCG on cells was further enhanced when vitamin D was taken at the same time [ 128 ]. Optimal levels of vitamin D have been shown to help prevent and regress low-grade squamous intraepithelial lesions of the cervix and reduce the risk of fibroids [ 266 ]. However, there is no clear statement of the exact mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that the VD-VDR signaling in cervical cancer cells can directly impact the expression of key oncogenes and tumor suppressor genes 47 , 48 . For instance, VDR activation has been shown to downregulate oncogenes like human cervical cancer oncogene-1 (HCCR-1) and upregulate tumor suppressors like p21 and p53, leading to cell cycle arrest and inhibition of cell proliferation 47 , 49 .…”
Section: Mechanisms Underlying the Vd-vdr Signaling In Cervical Cancermentioning
confidence: 99%
“… Synthesis and metabolism of VD 48 . VD is mostly produced by the skin under the influence of UVB radiation, although it can also be acquired through dietary sources.…”
Section: Figurementioning
confidence: 99%
“…Finally, in the kidney, 25(OH)3 undergoes another hydroxylation to produce 1.25 dihydroxycholecalciferol (1.25(OH)D3), also known as calcitriol, a potent secosteroid hormone. This has a mechanism of action comparable with those of the steroid hormones (estradiol and progesterone) [ 5 ]. It acts through interaction with the vitamin D receptor (VDR) and the RXR (retinoid X receptor) coreceptor, which are present in more than 30 different cell types, including the epithelium of the female reproductive tract [ 6 ].…”
Section: Introductionmentioning
confidence: 99%